Analisis Pengaruh Desain Tangki Mobil untuk Kapasitas 5000 Liter Gas Terhadap Tekanan Permukaan: The Impact of Surface Pressure on the Design of a 5,000-Liter Automobile Gas Tank - Faris Setio Wibowo; Delvis Agusman; Riyan Ariyansah (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2023)
The tank car is a closed storage area or tank designed to contain the liquid as a gas or liquid at a different pressure than the ambient pressure. Chemical reactions with the fluid inside a car's tank or physical phenomena the fluid encounters can cause instantaneous changes in the condition of the tank, resulting in occasional cracking or leaking. This research aims to determine how the design shape of a 5000-liter tank affects surface pressure. The method utilized is the finite element method based on computer-aided engineering (CAE) with the software Ansys Workbench Student Version. The results demonstrated that the maximal stress value and total deformation of the Model 2 tank were significantly different from those of the Model 1 and Model 3 tanks. The tank variation of the model is known to have the lowest stress value of 1.1309 MPa and the lowest deformation value of 0.0042421 mm. Therefore, the Model 2 tank variants are more recommended than the Models 1 and 3 for vehicles with a 5000-liter capacity.